Traffic legislation pertaining to mobile phone usage in Singapore : is it effective? - Kwek, Winnie (2013)
Prior research has shown that there is no significant difference in the risk of using hands-free (HF) and hands-held (HH) mobile phones while driving. This questions the effectiveness of the current traffic legislation pertaining to mobile phone usage in Singapore. Thus, this study seeks to gain insights regarding accident experience in Singapore, thereby evaluating the effectiveness of the legislation.